The Effect Of Hanging Ball Training On The Ability To Smash Roll Spike On Extracurricular Sepak Takraw In Senior High School Negeri 1 Kota Bengkulu - Pratama, Al Azis; Martiani, Martiani; Anggara, Deffri (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of hanging ball training on the ability to smash role spike in high school sepak takraw players in Bengkulu City. Using the total sampling method in knowing the number of respondents and obtained 12 respondents of sepak takraw players of SMA Negeri 1 Bengkulu City. This experimental research uses the design form One Group Pre test - Post test is a pre-experimental design in which there is a pre test (test before treatment) and post test (test after treatment) in one group. The data collection used is using test scores. Using descriptive data analysis techniques and t tests. The results of this study indicate that there is an effect of hanging ball training on the smash role spike ability of sepak takraw players of Bengkulu City State High School with a t value = 2.394 while the t table is 1.795 with a significant level α = 0.05 and dk = 12.